2015
DOI: 10.3109/03009734.2015.1072606
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of antibiotic resistance in nasopharyngeal bacterial isolates from healthy children in rural Uganda: A cross-sectional study

Abstract: Background: In Uganda, the main causes of death in children under 5 years of age are malaria and pneumonia—often due to delayed diagnosis and treatment. In preparation for a community case management intervention for pneumonia and malaria, the bacterial composition of the nasopharyngeal flora and its in vitro resistance were determined in children aged five or under to establish baseline resistance to commonly used antibiotics.Methods: In a population-based survey in April 2008, nasopharyngeal specimens were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 37 publications
6
62
5
Order By: Relevance
“…Both the Iganga/Mayuge and Kenyan studies were carried out prior to the introduction of PCV10 accounting for the difference in the carriage observed in our study. Different studies have shown varied carriage rates of pneumococci among children below ve years in Uganda and elsewhere [4,11,12] with most of them reporting a higher carriage rate than reported in our study. A systematic review reported a carriage rate in Africa to range between 21-94% [13] with more studies done among children than in adult population.…”
Section: Discussioncontrasting
confidence: 45%
“…Both the Iganga/Mayuge and Kenyan studies were carried out prior to the introduction of PCV10 accounting for the difference in the carriage observed in our study. Different studies have shown varied carriage rates of pneumococci among children below ve years in Uganda and elsewhere [4,11,12] with most of them reporting a higher carriage rate than reported in our study. A systematic review reported a carriage rate in Africa to range between 21-94% [13] with more studies done among children than in adult population.…”
Section: Discussioncontrasting
confidence: 45%
“…In the cRCT, community health workers (CHWs) were trained and equipped to provide community case management of malaria (control) or malaria and pneumonia (intervention) for children aged 6–59 months [25]. Data on antibiotic resistance from these surveys is presented elsewhere [26]. …”
Section: Methodsmentioning
confidence: 99%
“…The laboratory assays of identifying and isolating the bacterial isolates were performed as described in detail elsewhere [26]. In short, each swab was streaked on agar plates supplemented with 7% whole sheep blood and on chocolate agar.…”
Section: Methodsmentioning
confidence: 99%
“…KEYWORDS antibiotic resistance, Escherichia coli, Africa, protected areas, primates, class 1 integrons A ntibiotic resistance is ubiquitous in the developing world (1)(2)(3). In some African countries, resistance to commonly available antibiotics can exceed 75% (3)(4)(5)(6)(7)(8)(9). Cost, ease of use, and time on the market influence the use of antibiotics in Africa and the consequent resistance of bacteria to those antibiotics (10).…”
mentioning
confidence: 99%